Chemical Composition and, Cellular Evaluation of the Antioxidant Activity of Desmodium adscendens Leaves. (13th October 2010) - Muanda, François Nsemi; Bouayed, Jaouad; Djilani, Abdelouaheb; Yao, Chunyan; Soulimani, Rachid; Dicko, Amadou
Abstract : Desmodium adscendens plant is widely used as juice or tea in various parts of the world against a wide range of diseases. This study determines the quality and the quantity of polyphenols, flavonoids, anthocyanins, and tannins in D. adscendens leaves by UV-spectrophotometry and RP-HPLC methods. In addition, the antioxidant capacity of these phenolic compounds is evaluated by ABTS (2, 2 ′ -azino-bis(3-ethylbenzothiazoline-6-sulfonic)), DPPH (2, 2-diphenyl-1 picrylhydrazyl), and Cellular tests. D. adscendens leaves are mainly composite of flavonoid compounds with 12.8 mg of catechin equivalent (CE)/g dw. The amounts of total polyphenol compounds are 11.1 mg of gallic acid equivalent (GAE)/g dw. The quantity of total anthocyanin and total tannin compounds is not considerable 0.0182 mg CgE/g dw and 0.39 mg CE/g dw, respectively. A direct correlation between phenolic compounds and antioxidant activity is observed (R 2 = 0.96 ). The RP-HPLC analyses reveal that the main phenolic compound identified in the methanol-water extract is quercetrin dihydrat (2.11 mg/mL). According to the results, it is observed that D. adscendens leaves possess a considerable scavenging antioxidant and antiradical capacity, therefore these antioxidant properties might increase the therapeutic value of this medicinal plant.